(untitled) (Research, Society and Development, 2020)
The present study aimed to analyze the epidemiological profile of Malaria in the Amazon Region. This is an epidemiological, retrospective and descriptive study of a population nature, using secondary data, in which a survey of notified cases of Malaria in the Amazon Region, from 2010 to 2019, obtained in the Information System was carried out. of Notifiable Diseases (SINAN). Assessing aspects related to confirmed cases according to 1st year symptom (s), states of the Amazon Region, frequency in the extra-Amazon region, sex, age group, and parasitic species. Data were tabulated using the TABNET and Microsoft Office Excel 2019 programs. During the study period, 1,978,419 cases of Malaria were recorded in the Amazon Region. In 2010, the highest number of new cases was recorded (333,391), and in 2016, the smallest number (128,747) and pointed to a drop in the frequency of cases of Malaria from 2010 to 2016. In the distribution of cases in the Amazon Region, Amazonas state obtained 36% of the cases, followed by Pará, with 25%. In addition, 1,985,829 cases were recorded in the Amazon region and the country’s extra-Amazon region, with 0.4% (7,410) cases in the extra-Amazon region and 99.6% (1,978,419) in the Amazon region. There was a male prevalence (n = 1,204,127; 60%), the predominant age group was between 20 and 39 years old (n = 680,370; 34.4%). The presence of Malaria in the Region is remarkable, becoming a major challenge of a social, political and economic order, mainly due to its strong repercussions on the health of the population.